Electrical spin injection from highly spin polarized Co2CrAl Heusler alloy into non-magnetic p-Si semiconductor. Issue 185 (22nd November 2017) - Kar, Uddipta; Panda, J.; Nath, T. K.
ABSTRACT: Room temperature spin injection and detection in non-magnetic p-Si semiconductor have been studied in details in our Co2 CrAl (CCA)/MgO/p-Si heterojunction. The electrical transport properties have been investigated at different isothermal conditions in the temperature range of 30–300 K. We have found a giant spin accumulation in p-Si semiconductor using MgO/CCA tunnel junction. The accumulated spin decaying as a function of applied magnetic field for fixed bias current has been recorded. The spin life time (64 pS) and spin diffusion length (220 nm) have been estimated in this CCA/MgO/p-Si heterostructure at 300 K indicating its technological importance in spin-electronics device applications.